High-Profile Research and the Media: The Case of the Abio-Cor Artificial Heart - Morreim, E. Haavi (The Hastings Center report, 2004)
Public discussion of new medical trials is desirable, but not moment-by-moment disclosure of patients' ups and down. Nor is such disclosure necessary: the public is not entitled to all information about a trial as soon as it is available. What should be given the press, and what withheld, cannot be decided without appreciating the surprising number and intricate interrelations of the parties' needs and interests.